"أثر العدالة التنظيمية في تعزيز سلوك المواطنة التنظيمية في المؤسسة الاقتصادية -دراسة حالة المؤسسة الاستشفائية لطب العيون بالوادي- " - عبد الرؤوف, بوراس; سمير, محبوب; أبو بكر الصديق, عيساوي (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى التعرف على أثر العدالة التنظيمية في تعزيز سلوك المواطنة التنظيمية في المؤسسة الاستشفائية لطب العيون بالوادي، حيث تم التطرق في الجانب النظري إلى الأدبيات النظرية والدراسات السابقة، وفي الجانب التطبيقي تم استخدام الاستبيان لجمع بيانات من العاملين بالمؤسسة الإستشفائية لطب العيون بالوادي، لتحقيق أهداف الدراسة وفرضياتها. ومن أهم النتائج التي تم الحصول عليها هو وجود علاقة ذات دلالة إحصائية بين العدالة التنظيمية وأبعاد سلوك المواطنة التنظيمية ( الإيثار؛الكياسة؛ الروح الرياضية؛ السلوك الحضاري ووعي الضمير) و علاقة تأثير بين المتغيرين، كما تم التوصل إلى وجود فروق ذات دلالة إحصائية عند مستوى معنوية 5 %حول واقع العدالة التنظيمية في المؤسسة محل الدراسة تعزى لعامل الجنس؛ الجنسية؛ العمر و الرتبة الوظيفية، وعدم وجود فروق ذات دلالة إحصائية عند مستوى معنوية 5 %حول واقع العدالة التنظيمية في المؤسسة محل الدراسة تعزى لعامل الأقدمية. ""This study aims to identify the effect of organizational justice in enhancing the behavior of organizational citizenship in the hospital hospital for ophthalmology in the Eloued city, where the theoretical aspect was addressed to the theoretical literature and previous studies, and in the applied side the questionnaire was used to collect data from employees of the hospital for ophthalmology in the Eloued city, to achieve the goals and hypotheses of the study. Among the most important results obtained is the presence of a statistically significant relationship between organizational justice and the dimensions of organizational citizenship behavior (altruism; civility; mathematical spirit; civilized behavior and conscience consciousness) and an effect relationship between the two variables, Also, there were statistically significant differences at the 5% level of significance regarding the reality of organizational justice in the institution of study attributed to the sex factor. Nationality; age and job rank; And the absence of statistically significant differences at the 5% level of significance regarding the reality of organizational justice in the institution of study due to the seniority factor (professional experience). "
مذكرة ادارةاعمال ماستر
Keywords: العدالة التنظيمية، سلوك المواطنة التنظيمية، المؤسسة الإستشفائية لطب العيون بالوادي.; organizational justice, behavior of organizational citizenship, the Ophthalmology Hospital of the Eloued city.